Penerapan CRM Untuk Mempertahankan dan Menarik Pelanggan Baru Pada Toko Pakaian Yusni - Habibullah .; Herman Saputra; Wan Mariatul Kifti (Jurnal Teknologi Informasi dan Pendidikan, 2022)
The rapid development of technology in today's world has had a major impact on store performance in all areas of business, both in trading and service companies. In maintaining more advanced competitiveness, stores must continue to develop technology, another thing that needs to be considered in making the company more advanced is the relationship with customers which is also an important thing to always maintain. To manage good relationships with prospective customers and customers, the company uses Customer Relationship Management (CRM). CRM is a service to customers that is personal, to provide a consistent experience, so that it can provide customer satisfaction, and also get good relationships in the long term. By implementing a good CRM, stores will be easier to interact with potential customers and customers and provide information according to their needs. Customers can also get the information they need more quickly and easily. The Customer Relationship Management (CRM) System for Web-Based Information Services at Yusni's Clothing Store can make it easier for consumers who are in the village of base lunang, sub-district of kualauh leidong, district of Labuhan Batu Utara.